LEARNING MODEL OF DISASTER RESPONSE AS A PHYSICAL ACTIVITY IN ELEMENTARY SCHOOL STUDENTS - adi sumarsono (AL-ISHLAH: Jurnal Pendidikan, 2019)
This study aims to produce a type of game through physical activities that are in activies that are in accordance with physical education learning materials in elementary schools. This research also test the effectivenes of the products that have been produced. This development research methods refers to the Borg and Gall development step which consistes of ten development steps. The result of study are the creation of a type of game with the name og the name the game disaster response. The specifications of this game are the types of games that are carried out in the form of physical activities in which there are fundamental movements (locootor, non locomotor and manipulative motion). These three types of motion correspond to physical education materials in elementery schools. The results of this development product are saved in the form of VCD tutorial videos. The effectiveness test of this product was teted on two different schools and analyzed using a t test of significances 0,5 state that series of disarter response games are effective and appropriate to be used as physical education learning for elementary school students. Increased effectiveness is stated in the standard Gain which is in the category of “medium”. Throught this disaster response game it can be used as basic motion learning in elementary schools as well as providing preliminary material about emergency rescue efforts in the event of a natural disaster.